Implementation and analysis of hybrid communication for monitoring and control for android-based smart farming - Moh. Abdullah Anshori; Septriandi Wirayoga; Hadiwiyatno; Sri Wahyuni Dali (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2025)
Farmers are forced to water each crop individually or wait to switch off the water pump. to avoid this, water management needs to be optimized—that is, it needs to be done on schedule, in the appropriate quantity, and throughout a wide area in an effective manner. That is hybrid communication between online and offline communication. To run this system will use 3 nodes, for details 1 node in the irrigation section, 1 node in the monitoring section of land and soil quality, and 1 node in the section to control data or can be said to be a semi-server to give commands to 2 nodes offline. To see if the system still communicates with each other and runs according to the block diagram that has been designed, an Android application will be made to monitor the system. Where if there is a failed data update or data change in the results of the automation system, a notification will come out to check the system as a whole. To support this research, several sensor calibrations were carried out which resulted in an average accuracy level above 90 percent. For the overall system test, 10 experiments were carried out at different times to see the reliability of the system